Association between blood pressure and risk of cardiovascular hospital admissions among people with type 2 diabetes. Issue 18 (16th May 2014) - Yu, Dahai; Simmons, David
Abstract : Objective: To investigate the association between systolic and diastolic blood pressure (BP) and risk of hospitalisation among patients with type 2 diabetes. Methods: 4704 patients with type 2 diabetes from 18 general practices in Cambridgeshire were included. BP was assessed in 2008–2009. The primary outcome was cardiovascular hospital admissions in 2009–2011. Adjusted relative risks for each BP measurement group were estimated using Cox models. Further dose–response relationships between BP and risks were explored using restricted cubic spline models. Results: Over a median follow-up of 2 years, we recorded 5322 hospital admissions. There was a non-linear relationship between systolic (SBP) and diastolic (DBP) BP and the risk of cardiovascular hospitalisation (both p<0.001 for linearity test). The BP associated with the lowest risk of cardiovascular hospitalisation was 137 (95% CI 133 to 141)/78 (95% CI 76 to 80) mm Hg. The discrimination of the model could be significantly improved with either an SBP threshold or a DBP threshold (both p<0.0001). Conclusions: Among patients with type 2 diabetes, the risk of cardiovascular hospitalisation is lowest with a BP of 133–141/76–80 mm Hg. This concurs with the latest recommended randomised controlled trial based BP target of 140/80 from the American Diabetes Association.